Ventricular arrhythmia inducibility predicts clinical events in mitral valve prolapse syndrome - Benjamin Rath; Julian Wolfes; Christian Ellermann; Fatih Güner; Felix Wegner; Julia Köbe; Florian Reinke; Gerrit Frommeyer; Lars Eckardt (Clinical Research in Cardiology, 2026)
Abstract Background Mitral valve prolapse (MVP) is commonly benign, but an arrhythmic phenotype (AMVP) with increased risk for sudden cardiac death has been described. Current risk stratification is mainly based on clinical data and imaging markers, while the role of programmed ventricular stimulation (PVS) remains uncertain. Methods In this prospective single-center cohort study, 42 patients fulfilling the EHRA consensus criteria for AMVP underwent an electrophysiological study with programmed ventricular stimulation between 2016 and 2025. Stimulation was performed from the right ventricular apex and outflow tract using up to two extra stimuli. Following shared decision-making, patients received either an implantable cardioverter-defibrillator (ICD) or an implantable loop recorder (ILR). The endpoint was the occurrence of clinically significant ventricular arrhythmias (VAs), defined as appropriate ICD therapies, ILR-documented sustained VT, or arrhythmic syncope. Results Sustained ventricular arrhythmias were inducible in 20 patients (47.6%). ICD implantation was performed in 14 patients (70%) with inducible VA and in 6 patients (27.3%) without VA inducibility. During a mean follow-up of 38.0 ± 24.6 months, clinically significant VA occurred in 45.0% of patients with inducible VA vs. 9.1% of patients with nonpathological PVS ( p = 0.01). Conclusion Inducible ventricular arrhythmias during PVS were associated with subsequent clinically significant VA in AMVP. PVS may serve as an additional risk stratification tool in this entity.